2015
DOI: 10.1016/j.jnoncrysol.2014.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of Na2O–FeO–Fe2O3–P2O5 glasses

Abstract: The crystallization tendencies of five series of Na 2 O-FeO-Fe 2 O 3-P 2 O 5 (NFP) glasses with different O/P (3.0-3.5) and Fe/P (0.13-0.67) ratios were studied. Characteristic temperatures, including the glass transition temperature (T g) and crystallization temperature (T x h), were obtained using differential thermal analysis (DTA), and liquidus temperatures (T L) were determined by microscopic evaluation of heat-treated samples. The compositional dependence of glass structure and the characteristic tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…All of the investigated glasses evidenced a quite good thermal stability comparable with conventional silicate glasses for which K H value varied from 0.14 to about 1.3 [16,[27][28][29][30]. The increasing Na 2 SO 4 addition causes decrease in the K H parameter which means lowering the glass stability against crystallization and at the same ability of glass to vitrify on cooling [30].…”
Section: Dsc Analysis Of the Glassesmentioning
confidence: 79%
See 1 more Smart Citation
“…All of the investigated glasses evidenced a quite good thermal stability comparable with conventional silicate glasses for which K H value varied from 0.14 to about 1.3 [16,[27][28][29][30]. The increasing Na 2 SO 4 addition causes decrease in the K H parameter which means lowering the glass stability against crystallization and at the same ability of glass to vitrify on cooling [30].…”
Section: Dsc Analysis Of the Glassesmentioning
confidence: 79%
“…[22][23][24][25][26], and a nice comparison between them for iron phosphate glasses is given in [27], and most of those criterions show the similar dependence on glass composition. In case of iron phosphate glasses, one of the most frequently used is Hruby criterion, and therefore, the glass stability of the investigated materials was evaluated using it [16,27]. According to [22], the higher K H value, the greater would be its stability against crystallization.…”
Section: Dsc Analysis Of the Glassesmentioning
confidence: 99%
“…The oxide glasses have variety of applications in the daily use articles as well as advanced technological fields like protection of X-ray, fibre, optical instruments or lab glasswares. The thermal stability of Na 2 O-FeO-Fe 2 O 3 -P 2 O 5 was found to be poorer than sodium-free 75 iron phosphate glasses [28]. In present review article, Raman spectroscopic results for structures of borate, silicate, phosphate, borosilicate, borophosphate, aluminosilicate, phosphosilicate, alumino-borosilicate and tellurite glasses are summarized.…”
mentioning
confidence: 87%
“…For binary Fe‐phosphate glasses with O/P ratios between 3.0 and about 3.6, increasing the O/P ratio decreases T g , a trend consistent with the relative melting points of Fe(PO 3 ) 3 and Fe 4 (P 2 O 7 ) 3 (Figure ). Crystallization tendency was maximized for compositions with O/P ratios around 3.3‐3.4, with the metaphosphate (O/P = 3) and pyrophosphate (O/P = 3.5) compositions less likely to crystallize.…”
Section: Properties Of Iron Phosphate Glassesmentioning
confidence: 99%
“…Increasing the Fe/Na ratio in these pyrophosphate glasses increased the glass transition temperature, T g , and decreased its difference with the crystallization temperature ( T x ‐ T g ). Ma et al found a similar increase in crystallization tendency for pyrophosphate glasses with the replacement of Na 2 O with Fe 2 O 3 (O/P = 3.49) over the same compositional range, although melts with greater iron contents were less prone to crystallization. Adding high field strength oxides like Al 2 O 3 , B 2 O 3 , and SiO 2 increases the stability of iron phosphate melts against crystallization, whereas the additions of lower field strength oxides like the alkali and alkaline earths generally decrease stability against crystallization …”
Section: Properties Of Iron Phosphate Glassesmentioning
confidence: 99%